Marijuana use should not preclude consideration for kidney transplantation. Issue 10 (16th October 2019) - Fabbri, Kassandra R.; Anderson‐Haag, Tracy L.; Spenningsby, Anne M.; Israni, Ajay; Nygaard, Rachel M.; Stahler, Paul A.
Abstract: Transplant eligibility for tobacco and/or marijuana using candidates varies among transplant centers. This study compared the impact of marijuana use and tobacco use on kidney transplant recipient outcomes. Kidney transplant recipients at a single center from 2001 to 2015 were reviewed for outcomes of all‐cause graft loss, infection, biopsy‐proven acute rejection, and estimated glomerular filtration rate between four groups: marijuana‐only users, marijuana and tobacco users, tobacco‐only users, and nonusers. The cohort (N = 919) included 48 (5.2%) marijuana users, 45 (4.8%) marijuana and tobacco users, 136 (14.7%) tobacco users, and 75% nonusers. Smoking status was not significantly associated with acute rejection, estimated glomerular filtration rate or pneumonia within one‐year post‐transplant in an adjusted model. Compared to nonuse, marijuana and tobacco use and tobacco‐only use was significantly associated with increased risk of graft loss (aHR 1.68, P  = .034 and 1.52, P  = .006, respectively). Patients with isolated marijuana use had similar overall graft survival compared to nonusers (aHR 1.00, P  = .994). Marijuana use should not be an absolute contraindication to kidney transplant.